Multi-level structure hybrid supported atomic precision gold nanocluster catalyst and preparation method

Through the nanosheet-like array multi-stage structure LDH/rGO supported atomic precision gold nanocluster catalyst, the metal pollution and support stacking problems of alcohol selective oxidation catalyst are solved, and the catalytic effect with high activity and easy recovery is achieved, and benzyl alcohol is improved. Solvent-free oxidation properties.

CN114100629BInactive Publication Date: 2024-12-13BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111293447.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-03
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing alcohol-selective oxidation catalysts have metal contamination and difficulty in recycling in industrial applications, and single-carrier LDH nanosheets are prone to stacking, affecting catalytic activity. The van der Waals force between traditional graphene layers leads to insufficient active surface area. Exposed.

Method used

Captopril ligand-protected gold nanocluster catalyst was prepared by nanosheet-like array multi-stage structure LDH/rGO hybrid-loaded atomic precision gold nanocluster catalyst by separation through size focusing method and polyacrylamide gel electrophoresis, using pH double The electrostatic adsorption method is used to load it on a (M2+)Al-LDH/rGO support to form an Aun/(M2+)Al-LDH/rGO-T catalyst.

Benefits of technology

A high-activity and easy-to-recover green catalyst is achieved, which improves the solvent-free selective oxidation performance of benzyl alcohol, and has a small activity loss after multiple uses, providing a larger specific surface area and active sites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114100629B_ABST
    Figure CN114100629B_ABST
Patent Text Reader

Abstract

A multi-level structure hybrid supported atomic precision gold nanocluster catalyst and preparation method thereof. It belongs to the technical field of precious metal nanocatalysts. The catalyst expression is Au n / (M 2+ )Al‑LDH / rGO‑T, in which LDH nanosheets in the carrier grow vertically and staggered on both sides of rGO, where M 2+ Mg 2+ 、Ni 2+ 、Co 2+ Any one or two of the ions; Au n The Au nanoclusters are n=25, 38, and 127, which are highly dispersed at the edge of LDH nanosheets and at the interface between LDH and rGO. T represents the calcination temperature, which is 260-300°C. The captopril-protected Au n The nanoclusters are loaded on a hybrid support, and the ligands are removed by moderate calcination to obtain a catalyst. The advantage is that the obtained catalyst has a large specific surface area and more active sites. In the absence of an external base, the catalyst exhibits high activity and high selectivity in the solvent-free aerobic oxidation of benzyl alcohol to benzaldehyde.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of precious metal nanocatalysts, and specifically relates to a nanosheet array-type multi-level structure LDH / rGO hybrid loaded with atomic precision gold nanocluster catalyst and a preparation method thereof. Background Art

[0002] Selective oxidation of alcohols has become an important organic synthesis process because the corresponding aldehydes and ketones produced are important intermediates and precursors of medicines, pesticides, vitamins and fine chemicals. The catalysts commonly used to catalyze the selective oxidation of alcohols can be divided into homogeneous catalysts and heterogeneous catalysts. Homogeneous catalysts mainly include 2,2,6,6-tetramethylpiperidinyl-N-oxyl free radical (TEMPO), complexes of Ru and Pd, etc., which have uniform active centers and are easy to contact with reactants, thus showing high catalytic activity. However, due to the difficulty in separating them from the products and causing metal contamination, they have certain limitations in industrial applications. Therefore, in the alcohol catalytic oxidation reaction system, the development of efficient heterogeneous catalysts with high activity and selectivity, easy separation from reactants and recycling has attracted more and more attention from researchers. Compared with other precious metal catalysts (such as Pd, Pt and Ru, etc.), supported gold catalysts have the advantages of mild reaction conditions, not easy to be peroxidized and poisoned by strongly adsorbed by-products, etc. Therefore, they can be used as highly selective catalysts in the process of alcohol catalytic oxidation. In 2016, Zhang et al. [Wang S, Ying S, Chen G, Li L, Zhang H*. Catal. Sci. Technol. 2016.6:4090–4104.] reported the Au loading on hydrotalcite with different compositions. 25Nanocluster catalysts are highly efficient in catalyzing alcohol selective oxidation reactions in the absence of added base and with oxygen as the oxidant. In 2020, Zhang et al. [Xu Y, Li J, Zhou J, Liu Y, Wei Z, Zhang H*. J. Catal. 2020. 389: 409–420.] reported that nickel-aluminum hydrotalcite-loaded gold nanocluster catalysts with different atomic precision can efficiently catalyze the oxidation of benzyl alcohol in the absence of added base, with toluene as the solvent and air as the oxidant. However, single carrier LDH nanosheets will be severely stacked due to strong particle-particle interactions, and the use of organic solvents will inevitably cause environmental pollution. Graphene materials have the characteristics of large specific surface area, high conductivity and good chemical stability, and can be used in adsorption, electrochemistry, drug delivery and catalysis. However, the super strong van der Waals forces between graphene layers make it easy to stack, which is not conducive to the exposure of active surface area. Based on this, in 2016, Zhang et al. [Dou L, Zhang H*. J. Mater. Chem. A 2016, 4: 18990-19002.] prepared a CuMgAl-LDH / rGO hybrid with a nanosheet array structure by a simple and green citric acid-assisted liquid phase coprecipitation method, in which LDH nanosheets are vertically staggered and grown on both sides of the rGO sheet. This unique nanosheet array morphology has a large specific surface area, can provide more active sites, is conducive to enhancing its adsorption capacity for reaction substrates, and is expected to prepare highly dispersed atomic precision gold nanocluster catalysts. However, there has been no report on the atomic precision gold nanocluster catalyst loaded on the nanosheet array type multi-level structure hydrotalcite / reduced graphene oxide (LDH / rGO) hybrid. Summary of the invention

[0003] The purpose of the present invention is to provide a nanosheet array type hierarchical structure hydrotalcite / reduced graphene oxide hybrid (LDH / rGO) loaded with atomic precision gold nanocluster catalyst and a preparation method thereof. The present invention intends to use size focusing method and polyacrylamide gel electrophoresis separation technology to prepare atomic precision Au nanocluster catalyst protected by captopril (Capt) ligand. 25 Capt 18 、Au 38 Capt 24 and Au ~127 -Capt nanocluster precursor, with (M 2+ )Al-LDH / rGO hybrid (M 2+ Mg 2+ 、Ni 2+ 、Co 2+ ions) as carriers, and loaded onto the LDH / rGO hybrid carrier by pH dual-controlled electrostatic adsorption. 2+)The pI value of the Al-LDH / rGO hybrid carrier (~10.0) is greater than the pH value of the solution (pH~8.0), making (M 2+ ) The surface of the Al-LDH / rGO hybrid carrier is partially positively charged, and the pI of Au NCs (~5.6) is less than the pH value of the solution (~8.0), which makes the surface of Au NCs partially negatively charged. Under this condition, the negatively charged gold nanoclusters are adsorbed to the surface of the positively charged LDH / rGO nanosheets through strong electrostatic interaction to obtain the catalyst precursor. The obtained catalyst precursor is then moderately calcined to obtain atomic precision Au n Nanocluster Catalyst Au n / (M 2+ )A1-LDH / rGO-T, where Au n Nanoclusters (n is the number of gold atoms) are active components, and the obtained catalyst is used to catalyze the solvent-free aerobic oxidation reaction of benzyl alcohol in the absence of alkaline additives, providing a highly active and easily recyclable green catalyst.

[0004] The atomic precision gold nanocluster catalyst supported by the multi-level structure hybrid of the present invention is expressed as Au n / (M 2+ )A1-LDH / rGO-T, where Au n is n gold atoms, n = 25, 38, ~ 127; (M 2+ )A1-LDH / rGO 2+ Mg 2+ 、Ni 2+ 、Co 2+ Any one or two of the ions; characterized in that: the size is 55 to 70 nm and the thickness is 8 to 10 nm (M 2+ )Al-LDH nanosheets grow vertically and staggered on both sides of the rGO sheet, showing a nanosheet array morphology. The gold nanoclusters with sizes of 1.0±0.3, 1.5±0.3 and 1.8±0.4nm in the catalyst are highly dispersed at the edge of LDH and the junction of LDH and rGO; the active component in the catalyst is gold nanoclusters, and its mass percentage is 0.5-1.5wt%. The unique nanosheet array morphology of the obtained catalyst has a large specific surface area, can provide more active sites, and enhance the adsorption capacity of the reaction substrate. It has a greatly improved solvent-free selective oxidation performance of benzyl alcohol compared with traditional nano-gold catalysts.

[0005] The method for preparing the gold nanocluster catalyst of the present invention is a pH dual-controlled electrostatic adsorption method. Atomic precision gold nanoclusters protected by captopril ligands are prepared as precursors by size focusing method and polyacrylamide gel electrophoresis separation technology, and a simple and green citric acid-assisted liquid phase coprecipitation method is used to prepare nanosheet array-type multi-level structures (M 2+)A1-LDH / rGO hybrid (where M 2+ Mg 2+ 、Ni 2+ 、Co 2+ ions) as carriers, and by finely adjusting the pH value to 6-10, gold nanoclusters were loaded onto (M 2+ )A1-LDH / rGO hybrid carrier, after moderate calcination to remove the ligand, a nanosheet array-like hierarchical structure LDH / rGO hybrid supported atomic precision gold nanocluster catalyst was obtained, named Au n / (M 2+ )A1-LDH / rGO-T. The specific preparation process is:

[0006] (1) The synthesis of gold nanocluster precursors was prepared according to the method reported by Zhang et al. in Journal of Catalysis, 389 (2020), 409–420.

[0007] Preparation of Au by combining size focusing and polyacrylamide gel electrophoresis 25 Capt 18 、Au 38 Capt 24 and Au ~127-Capt nanoclusters. First, 1g of tetrahydrated chloroauric acid was dissolved in 100mL of methanol to prepare a 10mg / mL chloroauric acid methanol stock solution; then, 8.23mL of tetrahydrated chloroauric acid (HAuCl4·4H2O, 0.20mmol) methanol solution and 126.8mg of tetraoctylammonium bromide (TOABr, 0.23mmol) were added to a 100mL round-bottom flask containing 6.75mL of methanol, and magnetically stirred at 1200rpm at room temperature, and the mixed solution changed from orange-yellow to dark red. After 15 minutes of reaction, 130.4mg of captopril (Capt, 0.60mmol) was added to the reaction solution, and the color of the solution quickly changed to white. After 30 minutes of reaction, the stirring rate was adjusted to 600rpm, and 5mL of NaBH4 ice water solution (1mmol, 37.8mg dissolved in 5mL of ice water) was quickly added to the above reaction solution, and the color of the solution immediately changed to brown-green. After the above reaction solution was reacted in a water bath at 25±1°C for 48 hours, the reaction solution was centrifuged (5000r / min, 20min) to remove the unreacted and insoluble Au(I):Capt polymer. The supernatant was collected and concentrated by rotary evaporation (30°C, 20min). 20mL of acetone was added to the concentrate and allowed to stand for 12 hours to obtain precipitated gold clusters. Then it was vacuum dried at 30°C for 12 hours to obtain a crude product. The crude product was extracted with methanol for 6 times (0.5-1mL each time) to obtain a brown-black transparent extract. 20mL of acetone was added to the brown-black transparent extract to precipitate the gold clusters again, and centrifuged (3000r / min, 10min) to obtain a brown-black precipitate. It was vacuum dried at 30°C for 12 hours to obtain the final brown-black product Au : Capt nanoclusters.

[0008] Polyacrylamide gel electrophoresis separation: The obtained Au:Capt product was separated by polyacrylamide gel electrophoresis (PAGE) at 300V by using a vertical gel electrophoresis system. The separation gel and stacking gel were prepared with 30% and 4% acrylamide monomers, respectively. The Au:Capt clusters were dissolved in 10% (v / v) glycerol / water at a concentration of 30 mg / mL and added to the gel at a loading amount of 40 μL / well. After 4 hours of electrophoretic separation, clear bands were cut out from the gel and soaked in water for 2 hours, and the nanocluster solutions mixed with the gel matrix were filtered by using a 0.22 μm filter. Then, after acidification with 10% (v / v) glacial acetic acid, the acidified nanocluster solution was concentrated using a 3 kDa cutoff filter, and finally the concentrate was precipitated with acetone and dried under vacuum for 12 hours to obtain pure Au. 25 Capt 18 and Au 38 Capt 24As for the larger gold nanoclusters, we used a simple method, assuming that the gold nanoclusters are spherical and have the same density as the bulk Au. Based on the size of ~1.6 nm obtained by TEM analysis, we calculated that the larger gold nanoclusters correspond to Au ~127 -Capt.

[0009] (2) Preparation of nanosheet array-type hierarchical structured hydrotalcite / reduced graphene oxide hybrid carrier.

[0010] Firstly, natural flake graphite powder was used as raw material to prepare graphene oxide (GO) sol (ρ=8.07 mg / mL) by the improved Hummers method as a stock solution. Then, a nanosheet array-type multi-level structure (MGO) was prepared by a simple and green citric acid-assisted liquid phase coprecipitation method. 2+ )Al-LDH / rGO hybrid (where M 2+ Mg 2+ 、Ni 2+ 、Co 2+ ions). The specific steps are as follows: 50 mg of GO sol was dispersed in 100 mL of deionized water, and ultrasonic stripping was performed for 20 minutes. Then 25 mg of citric acid was added and ultrasonic stripping was continued for 5 minutes to obtain a citric acid-modified GO suspension. The obtained citric acid-modified GO suspension was transferred to a 500 mL four-necked flask, and a mixed alkaline solution of NaOH and Na2CO3 ([OH-] / [CO3 2 -]=3.2, [CO3 2 -] / [Al 3+ ]=2,200mL) to pH=10.0±0.1, and stabilize for 10 minutes. Then add 100mL (M 2+ )(NO3)2·6H2O (M=Mg, Co, Ni) (15mmol) and Al(NO3)3·9H2O (5mmol) mixed salt solution, and mixed alkali solution was added dropwise to make the pH value of the system 10.0±0.1. After the addition was completed, the resulting reaction solution was crystallized in a 65℃ water bath for 4 hours. Finally, it was centrifuged, washed with deionized water until neutral, and freeze-dried to obtain a nanosheet array structure hybrid carrier, named (M 2+ )Al-LDH / rGO.

[0011] (3) Synthesis of nanosheet array-like hierarchical structured LDH / rGO-loaded atomically precise gold nanocluster catalysts

[0012] Preparation of Au by pH dual-controlled electrostatic adsorption n / (M 2+ )Al-LDH / rGO-T catalyst (where M 2+ Mg2+ 、Ni 2+ 、Co 2+ ions, any one or two), the specific steps are as follows: 0.5-1.0g (M 2+ ) The Al-LDH / rGO hybrid carrier is added to 30-50 mL of deionized water, and an appropriate amount of a certain concentration of Na2CO3 solution (0.1 mol / L) is added for ultrasonic dispersion for 5-15 minutes to obtain a carrier dispersion with a pH of 6.0-8.0. Stir vigorously at room temperature, add a certain amount of gold nanocluster precursor solution pre-adjusted to pH 6.0-10.0 with a certain concentration of Na2CO3 solution to the above carrier dispersion, the theoretical loading of the gold nanocluster is 0.5-1.5 wt%, and react with magnetic stirring at 1000 rpm for 2-6 hours. Collect the mixture by centrifugation and freeze-dry to obtain a catalyst precursor. The obtained catalyst precursor is calcined at 260-300°C in a nitrogen atmosphere for 3 hours to obtain a catalyst, named Au n / (M 2+ )Al-LDH / rGO-T.

[0013] The nanosheet array-type multi-level structure LDH / rGO loaded atomic precision gold nanocluster catalyst needs to be sealed and stored.

[0014] The nanosheet array-type multi-level structure LDH / rGO loaded atomic precision gold nanocluster catalyst described in the present invention can be applied to the solvent-free aerobic oxidation reaction of benzyl alcohol.

[0015] The catalyst obtained after the reaction separation can be recycled after drying.

[0016] The main advantages of the present invention are:

[0017] (1) Provided is a novel nanosheet array-type multi-level structure LDH / rGO loaded atomic precision gold nanocluster catalyst and its preparation method. 2+ )Al-LDH nanosheets grow vertically and staggered on both sides of the rGO sheets, showing a nanosheet array-like morphology. This unique morphology effectively prevents the self-aggregation between LDH nanosheets and rGO sheets, which is beneficial to increase the specific surface area of ​​the catalyst and expose more effective Au active sites.

[0018] (2) The nanosheet array-type hierarchical structure LDH / rGO loaded atomic precision gold nanocluster catalyst prepared by pH dual-controlled electrostatic adsorption method has the characteristics of large specific surface area, high dispersion of active components and more active sites. It has obvious performance advantages in catalyzing the solvent-free oxidation reaction of benzyl alcohol under the conditions of no alkaline additives and molecular oxygen as oxidant, and there is no obvious loss of activity after repeated use for 5 times. It provides a new path for the synthesis of inorganic hierarchical structure nanocomposites. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is the atomic precision Au in Example 1 25 Capt 18 HRTEM image of nanoclusters.

[0020] Figure 2 is the atomic precision Au in Example 12 38 Capt 24 HRTEM image of nanoclusters.

[0021] Figure 3 The nanosheet array-like multi-level structure nickel aluminum hydrotalcite / reduced graphene oxide hybrid loaded with atomic precision Au obtained under the condition of adjusting pH to 6.0 in Example 1 25 Capt 18 HRTEM image of the nanocluster catalyst.

[0022] Figure 4 The nanosheet array type multi-level structure nickel aluminum hydrotalcite / reduced graphene oxide hybrid loaded with atomic precision Au obtained under the condition of adjusting pH to 10.0 in Example 2 25 Capt 18 HRTEM image of the nanocluster catalyst.

[0023] Figure 5 The nanosheet array-like multi-level structure nickel aluminum hydrotalcite / reduced graphene oxide hybrid loaded with atomic precision Au obtained under the condition of adjusting pH to 8.0 in Example 3 25 Capt 18 HRTEM image of the nanocluster catalyst.

[0024] Figure 6 The nanosheet array type multi-level structure nickel magnesium aluminum hydrotalcite / reduced graphene oxide hybrid loaded with atomic precision Au in Example 12 38 Capt 24 HRTEM image of the nanocluster catalyst. DETAILED DESCRIPTION

[0025] The present invention is described in detail below by way of examples, but the present invention is not limited to the following examples.

[0026] Example 1

[0027] (1) Au 25 Capt 18 Preparation of nanoclusters

[0028] Weigh 1.0g of HAuCl4·4H2O into 100mL of methanol to prepare a 10mg / mL chloroauric acid methanol solution. Add 24.69mL of the above solution and 0.3804g of TOABr (0.69mmol) into a 100mL single-necked flask containing 20.31mL of methanol. Stir magnetically at 1200rpm in a 25±1℃ water bath, and the mixture changes from orange-yellow to dark red. After 15 minutes, 0.3912g of captopril (0.60mmol) is added to the reaction solution, and the color of the solution quickly changes to white. After 30 minutes of reaction, the stirring rate is adjusted to 600rpm, and 15mL of NaBH4 ice water solution is quickly added to the above reaction solution, and the color of the solution immediately changes to brown-green. After the above reaction solution is continuously reacted in a 25℃ water bath for 48 hours, it is centrifuged (4800r / min, 20min) to remove the unreacted and insoluble Au(I):Capt polymer. The supernatant was collected and concentrated by rotary evaporation (30°C, 20 min). 20 mL of acetone was added to the concentrate and allowed to stand for 12 hours to obtain precipitated gold clusters. The crude product was then vacuum dried at 30°C for 12 hours to obtain a crude product. The crude product was extracted with methanol for 6 consecutive times (0.5-1 mL each time) to obtain a brown-black transparent extract. 20 mL of acetone was added to the brown-black transparent extract to precipitate the gold clusters again, and centrifuged (3000 r / min, 10 min) to obtain a brown-black precipitate. It was vacuum dried at 30°C for 12 hours to obtain the final brown-black product Au. : Capt nanoclusters.

[0029] Polyacrylamide gel electrophoresis separation: The obtained Au:Capt product was separated by polyacrylamide gel electrophoresis (PAGE) at 300V using a vertical gel electrophoresis system. The separation gel and stacking gel were prepared with 30% and 4% acrylamide monomers, respectively. The Au:Capt clusters were dissolved in 10% (v / v) glycerol / water at a concentration of 30 mg / mL and added to the gel at a loading amount of 40 μL / well. After 4 hours of electrophoretic separation, clear bands were cut out from the gel and soaked in water for 2 hours, and the nanocluster solutions mixed with the gel matrix were filtered by using a 0.22 μm filter. Then, after acidification with 10% (v / v) glacial acetic acid, the acidified nanocluster solution was concentrated using a 3 kDa cutoff filter, and finally the concentrate was precipitated with acetone and dried under vacuum to obtain one of the pure black-brown solid powders, which was recorded as Au 25 Capt 18 .

[0030] (2) Preparation of Ni3Al-LDH / rGO hybrid support

[0031] Ni(NO3)2·6H2O and Al(NO3)3·9H2O were mixed in a molar ratio of [Ni 2+ ] / [A13+ ]=3, prepare 100mL salt solution ([Ni 2+ ]+[A1 3+ ]=2mol·L -1 ), and NaOH and Na2CO3 ([OH-] / [CO3 2- ]=3.2, [CO3 2- ] / [A1 3+ ]=3) Prepare 100mL of mixed alkali solution with deionized water. Disperse 50mg GO sol into 100mL of deionized water, ultrasonically exfoliate for 20 minutes to obtain exfoliated graphene oxide, and then add 25mg citric acid and continue ultrasonication for 5 minutes. The obtained citric acid-modified GO suspension was transferred to a 500mL four-necked flask, and the mixed alkali solution was added dropwise to pH=10.0±0.1 under vigorous stirring, and stabilized for 10 minutes. Then add the mixed salt solution dropwise, and at the same time add the mixed alkali solution dropwise so that the pH value of the mixed system is 10.0±0.1. After the addition is completed, the resulting reaction solution is crystallized in a 65℃ water bath for 4 hours. Finally, it is separated by centrifugation, washed with deionized water until neutral, and freeze-dried to obtain a brown-green solid powder, named Ni3Al-LDH / rGO.

[0032] (3) Au 25 Preparation of / Ni3Al-LDH / rGO catalyst

[0033] 25 mg Au 25 Capt 18 The nanoclusters were dissolved in 100 mL of deionized water to obtain 0.25 mg / mL Au 25 Capt 18 Aqueous solution. Place 1.0 g of Ni3Al-LDH / rGO hybrid carrier in a 150 mL beaker, add 50 mL of deionized water and ultrasonicate for 5 minutes to obtain a hybrid carrier dispersion with a pH of ~ 6.0. Measure 20 mL of 0.25 mg / mL Au 25 Capt 18 Aqueous solution, add an appropriate amount of 0.1 mol / L sodium carbonate solution to pre-adjust the pH to 8.0, add it to the above carrier dispersion under vigorous stirring, the theoretical loading amount of gold nanoclusters is 0.5wt%, stir at 1000rpm for 4 hours. Collect the mixture by centrifugation and freeze-dry to obtain the catalyst precursor Au 25 Capt 18 / Ni3Al-LDH / rGO. The obtained catalyst precursor was calcined at 270°C for 3 hours in a nitrogen atmosphere to obtain a catalyst named 0.5-Au 25 / Ni3Al-LDH / rGO-270.

[0034] Example 2

[0035] (1) Au 25 Capt 18 The preparation of nanoclusters is the same as in Example 1.

[0036] (2) The preparation of Ni3Al-LDH / rGO hybrid carrier is the same as that in Example 1.

[0037] (3) Au 25 Preparation of / Ni3Al-LDH / rGO catalyst

[0038] 25 mg Au 25 Capt 18 The nanoclusters were dissolved in 100 mL of deionized water to obtain 0.25 mg / mL Au 25 Capt 18 Aqueous solution. Place 1.0 g of Ni3Al-LDH / rGO hybrid carrier in a 150 mL beaker, add 50 mL of deionized water and an appropriate amount of 0.1 mol / L sodium carbonate solution, and adjust the pH of the hybrid carrier dispersion to 10.0 after ultrasonic treatment for 15 minutes. Measure 20 mL of 0.25 mg / mL Au 25 Capt 18 Aqueous solution, add an appropriate amount of 0.1 mol / L sodium carbonate solution to pre-adjust the pH to 8.0, add it to the above carrier dispersion under vigorous stirring, the theoretical loading amount of gold nanoclusters is 0.5wt%, stir at 1000rpm for 4 hours. Collect the mixture by centrifugation and freeze-dry to obtain the catalyst precursor Au 25 Capt 18 / Ni3Al-LDH / rGO. The obtained catalyst precursor was calcined at 270°C for 3 hours in a nitrogen atmosphere to obtain a catalyst named 0.5-Au 25 / Ni3Al-LDH / rGO-270.

[0039] Example 3

[0040] (1) Au 25 Capt 18 The preparation of nanoclusters is the same as in Example 1.

[0041] (2) The preparation of Ni3Al-LDH / rGO hybrid carrier is the same as that in Example 1.

[0042] (3) Au 25 Preparation of / Ni3Al-LDH / rGO catalyst

[0043] 25 mg Au 25 Capt 18 The nanoclusters were dissolved in 100 mL of deionized water to obtain 0.25 mg / mL Au25 Capt 18 Aqueous solution. Place 1.0 g of Ni3Al-LDH / rGO hybrid carrier in a 150 mL beaker, add 50 mL of deionized water and an appropriate amount of 0.1 mol / L sodium carbonate solution, and adjust the pH of the hybrid carrier dispersion to 8.0 after ultrasonic treatment for 10 minutes. Measure 20 mL of 0.25 mg / mL Au 25 Capt 18 Aqueous solution, add an appropriate amount of 0.1 mol / L sodium carbonate solution to pre-adjust the pH to 8.0, add it to the above carrier dispersion under vigorous stirring, the theoretical loading amount of gold nanoclusters is 0.5wt%, stir at 1000rpm for 4 hours. Collect the mixture by centrifugation and freeze-dry to obtain the catalyst precursor Au 25 Capt 18 / Ni3Al-LDH / rGO. The obtained catalyst precursor was calcined at 270°C for 3 hours in a nitrogen atmosphere to obtain a catalyst named 0.5-Au 25 / Ni3Al-LDH / rGO-270.

[0044] Example 4

[0045] (1) Au 25 Capt 18 The preparation of nanoclusters is the same as in Example 1.

[0046] (2) The preparation of Ni3Al-LDH / rGO hybrid carrier is the same as that in Example 1.

[0047] (3) Au 25 Preparation of / Ni3Al-LDH / rGO catalyst

[0048] 25 mg Au 25 Capt 18 The nanoclusters were dissolved in 100 mL of deionized water to obtain 0.25 mg / mL Au 25 Capt 18 Aqueous solution. Place 1.0 g of Ni3Al-LDH / rGO hybrid carrier in a 150 mL beaker, add 50 mL of deionized water and an appropriate amount of 0.1 mol / L sodium carbonate solution, and adjust the pH of the hybrid carrier dispersion to 8.0 after ultrasonic treatment for 10 minutes. Measure 20 mL of 0.25 mg / mL Au 25 Capt 18 Aqueous solution, add an appropriate amount of 0.1 mol / L sodium carbonate solution to pre-adjust the pH to 6.0, add it to the above carrier dispersion under vigorous stirring, the theoretical loading amount of gold nanoclusters is 0.5wt%, stir at 1000rpm for 4 hours. Collect the mixture by centrifugation and freeze-dry to obtain the catalyst precursor Au 25Capt 18 / Ni3Al-LDH / rGO. The obtained catalyst precursor was calcined at 270°C for 3 hours in a nitrogen atmosphere to obtain a catalyst named 0.5-Au 25 / Ni3Al-LDH / rGO-270.

[0049] Example 5

[0050] (1) Au 25 Capt 18 The preparation of nanoclusters is the same as in Example 1.

[0051] (2) The preparation of Ni3Al-LDH / rGO hybrid carrier is the same as that in Example 1.

[0052] (3) Au 25 Preparation of / Ni3Al-LDH / rGO catalyst

[0053] 25 mg Au 25 Capt 18 The nanoclusters were dissolved in 100 mL of deionized water to obtain 0.25 mg / mL Au 25 Capt 18 Aqueous solution. Place 1.0 g of Ni3Al-LDH / rGO hybrid carrier in a 150 mL beaker, add 50 mL of deionized water and an appropriate amount of 0.1 mol / L sodium carbonate solution, and adjust the pH of the hybrid carrier dispersion to 8.0 after ultrasonic treatment for 10 minutes. Measure 20 mL of 0.25 mg / mL Au 25 Capt 18 Aqueous solution, add an appropriate amount of 0.1 mol / L sodium carbonate solution to pre-adjust the pH to 10.0, add it to the above carrier dispersion under vigorous stirring, the theoretical loading amount of gold nanoclusters is 0.5wt%, stir at 1000rpm for 4 hours. Collect the mixture by centrifugation and freeze-dry to obtain the catalyst precursor Au 25 Capt 18 / Ni3Al-LDH / rGO. The obtained catalyst precursor was calcined at 270°C for 3 hours in a nitrogen atmosphere to obtain a catalyst named 0.5-Au 25 / Ni3Al-LDH / rGO-270.

[0054] Example 6

[0055] (1) Au 25 Capt 18 The preparation of nanoclusters is the same as in Example 1.

[0056] (2) The preparation of Ni3Al-LDH / rGO hybrid carrier is the same as that in Example 1.

[0057] (3) Au 25 Preparation of / Ni3Al-LDH / rGO catalyst

[0058] 25 mg Au 25 Capt 18 The nanoclusters were dissolved in 100 mL of deionized water to obtain 0.25 mg / mL Au 25 Capt 18 Aqueous solution. Place 1.0 g of Ni3Al-LDH / rGO hybrid carrier in a 150 mL beaker, add 50 mL of deionized water and an appropriate amount of 0.1 mol / L sodium carbonate solution, and adjust the pH of the hybrid carrier dispersion to 8.0 after ultrasonic treatment for 10 minutes. Measure 20 mL of 0.25 mg / mL Au 25 Capt 18 Aqueous solution, add an appropriate amount of 0.1 mol / L sodium carbonate solution to pre-adjust the pH to 8.0, add it to the above carrier dispersion under vigorous stirring, the theoretical loading amount of gold nanoclusters is 0.5wt%, stir at 1000rpm for 2 hours. Collect the mixture by centrifugation and freeze-dry to obtain the catalyst precursor Au 25 Capt 18 / Ni3Al-LDH / rGO. The obtained catalyst precursor was calcined at 270°C for 3 hours in a nitrogen atmosphere to obtain a catalyst named 0.5-Au 25 / Ni3Al-LDH / rGO-270.

[0059] Example 7

[0060] (1) Au 25 Capt 18 The preparation of nanoclusters is the same as in Example 1.

[0061] (2) The preparation of Ni3Al-LDH / rGO hybrid carrier is the same as that in Example 1.

[0062] (3) Au 25 Preparation of / Ni3Al-LDH / rGO catalyst

[0063] 25 mg Au 25 Capt 18 The nanoclusters were dissolved in 100 mL of deionized water to obtain 0.25 mg / mL Au 25 Capt 18 Aqueous solution. Place 1.0 g of Ni3Al-LDH / rGO hybrid carrier in a 150 mL beaker, add 50 mL of deionized water and an appropriate amount of 0.1 mol / L sodium carbonate solution, and adjust the pH of the hybrid carrier dispersion to 8.0 after ultrasonic treatment for 10 minutes. Measure 20 mL of 0.25 mg / mL Au 25Capt 18 Aqueous solution, add an appropriate amount of 0.1 mol / L sodium carbonate solution to pre-adjust the pH to 8.0, add it to the above carrier dispersion under vigorous stirring, the theoretical loading amount of gold nanoclusters is 0.5wt%, stir at 1000rpm for 6 hours. Collect the mixture by centrifugation and freeze-dry to obtain the catalyst precursor Au 25 Capt 18 / Ni3Al-LDH / rGO. The obtained catalyst precursor was calcined at 270°C for 3 hours in a nitrogen atmosphere to obtain a catalyst named 0.5-Au 25 / Ni3Al-LDH / rGO-270.

[0064] Example 8

[0065] (1) Au 25 Capt 18 The preparation of nanoclusters is the same as in Example 1.

[0066] (2) The preparation of Ni3Al-LDH / rGO hybrid carrier is the same as that in Example 1.

[0067] (3) Au 25 Preparation of / Ni3Al-LDH / rGO catalyst

[0068] 25 mg Au 25 Capt 18 The nanoclusters were dissolved in 100 mL of deionized water to obtain 0.25 mg / mL Au 25 Capt 18 Aqueous solution. Place 1.0 g of Ni3Al-LDH / rGO hybrid carrier in a 150 mL beaker, add 50 mL of deionized water and an appropriate amount of 0.1 mol / L sodium carbonate solution, and adjust the pH of the hybrid carrier dispersion to 8.0 after ultrasonic treatment for 10 minutes. Measure 60 mL of 0.25 mg / mL Au 25 Capt 18 Aqueous solution, add an appropriate amount of 0.1 mol / L sodium carbonate solution to pre-adjust the pH to 8.0, add it to the above-mentioned carrier dispersion under vigorous stirring, the theoretical loading amount of gold nanoclusters is 1.5wt%, stir at 1000rpm for 4 hours. Collect the mixture by centrifugation and freeze-dry to obtain the catalyst precursor Au 25 Capt 18 / Ni3Al-LDH / rGO. The obtained catalyst precursor was calcined at 270°C for 3 hours in a nitrogen atmosphere to obtain a catalyst named 1.5-Au 25 / Ni3Al-LDH / rGO-270.

[0069] Example 9

[0070] (1) Au 25 Capt 18 The preparation of nanoclusters is the same as in Example 1.

[0071] (2)Ni 1.5 Mg 1.5 Preparation of Al-LDH / rGO hybrid support

[0072] Ni(NO3)2·6H2O, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were mixed in a molar ratio of [M 2+ ] / [A1 3+ ]=3([Ni 2+ ] / [Mg 3+ ]=1), prepare 100mL salt solution ([M 2+ ]+[A1 3+ ]=2mol·L -1 ), and NaOH and Na2CO3 ([OH-] / [CO3 2 -]=3.2, [CO3 2 -] / [A1 3+ ]=3) Use deionized water to prepare 100mL of mixed alkali solution. Disperse 50mg GO sol in 100mL of deionized water, ultrasonically exfoliate for 20 minutes to obtain exfoliated graphene oxide, and then add 25mg citric acid and continue ultrasonication for 5 minutes. The obtained citric acid-modified GO suspension was transferred to a 500mL four-necked flask, and the mixed alkali solution was added dropwise under vigorous stirring until the pH = 10.0±0.1, and stabilized for 10 minutes. Then add the mixed salt solution dropwise, and at the same time add the mixed alkali solution so that the pH value of the mixed system is 10.0±0.1. After the addition is completed, the resulting reaction solution is crystallized in a 65°C water bath for 4 hours. Finally, it is separated by centrifugation, washed with deionized water until neutral, and freeze-dried to obtain a brown-green solid powder, named Ni 1.5 Mg 1.5 Al-LDH / rGO.

[0073] (3) Au 25 / Ni 1.5 Mg 1.5 Preparation of Al-LDH / rGO catalyst

[0074] 25 mg Au 25 Capt 18 The nanoclusters were dissolved in 100 mL of deionized water to obtain 0.25 mg / mL Au 25 Capt 18 1.0g of Ni 1.5 Mg 1.5The Al-LDH / rGO hybrid carrier was placed in a 150 mL beaker, and 50 mL of deionized water and an appropriate amount of 0.1 mol / L sodium carbonate solution were added and ultrasonicated for 10 minutes to obtain a hybrid carrier dispersion with a pH of 8.0. 40 mL of 0.25 mg / mL Au 25 Capt 18 Aqueous solution, add an appropriate amount of 0.1 mol / L sodium carbonate solution to pre-adjust the pH to 8.0, add it to the above carrier dispersion under vigorous stirring, the theoretical loading amount of gold nanoclusters is 1.0wt%, stir at 1000rpm for 4 hours. Collect the mixture by centrifugation and freeze-dry to obtain the catalyst precursor Au 25 Capt 18 / Ni 1.5 Mg 1.5 The obtained catalyst precursor was calcined at 280°C for 3 hours in a nitrogen atmosphere to obtain a catalyst named 1-Au 25 / Ni 1.5 Mg 1.5 Al-LDH / rGO-280.

[0075] Example 10

[0076] (1) Au 25 Capt 18 The preparation of nanoclusters is the same as in Example 1.

[0077] (2)Ni 1.5 Mg 1.5 The preparation of Al-LDH / rGO hybrid carrier is the same as Example 9.

[0078] (3) Au 25 / Ni 1.5 Mg 1.5 Preparation of Al-LDH / rGO catalyst

[0079] 25 mg Au 25 Capt 18 The nanoclusters were dissolved in 100 mL of deionized water to obtain 0.25 mg / mL Au 25 Capt 18 1.0g of Ni 1.5 Mg 1.5 The Al-LDH / rGO hybrid carrier was placed in a 150 mL beaker, and 50 mL of deionized water and an appropriate amount of 0.1 mol / L sodium carbonate solution were added and ultrasonicated for 10 minutes to obtain a hybrid carrier dispersion with a pH of 8.0. 40 mL of 0.25 mg / mL Au 25 Capt 18Aqueous solution, add an appropriate amount of 0.1 mol / L sodium carbonate solution to pre-adjust the pH to 8.0, add it to the above carrier dispersion under vigorous stirring, the theoretical loading amount of gold nanoclusters is 1.0wt%, stir at 1000rpm for 4 hours. Collect the mixture by centrifugation and freeze-dry to obtain the catalyst precursor Au 25 Capt 18 / Ni 1.5 Mg 1.5 The obtained catalyst precursor was calcined at 260°C for 3 hours in a nitrogen atmosphere to obtain a catalyst named 1-Au 25 / Ni 1.5 Mg 1.5 Al-LDH / rGO-260.

[0080] Embodiment 11

[0081] (1) Au 25 Capt 18 The preparation of nanoclusters is the same as in Example 1.

[0082] (2)Ni 1.5 Mg 1.5 The preparation of Al-LDH / rGO hybrid carrier is the same as Example 9.

[0083] (3) Au 25 / Ni 1.5 Mg 1.5 Preparation of Al-LDH / rGO catalyst

[0084] 25 mg Au 25 Capt 18 The nanoclusters were dissolved in 100 mL of deionized water to obtain 0.25 mg / mL Au 25 Capt 18 1.0g of Ni 1.5 Mg 1.5 The Al-LDH / rGO hybrid carrier was placed in a 150 mL beaker, and 50 mL of deionized water and an appropriate amount of 0.1 mol / L sodium carbonate solution were added and ultrasonicated for 10 minutes to obtain a hybrid carrier dispersion with a pH of 8.0. 40 mL of 0.25 mg / mL Au 25 Capt 18 Aqueous solution, add an appropriate amount of 0.1 mol / L sodium carbonate solution to pre-adjust the pH to 8.0, add it to the above carrier dispersion under vigorous stirring, the theoretical loading amount of gold nanoclusters is 1.0wt%, stir at 1000rpm for 4 hours. Collect the mixture by centrifugation and freeze-dry to obtain the catalyst precursor Au 25 Capt 18 / Ni 1.5 Mg1.5 The obtained catalyst precursor was calcined at 300°C for 3 hours in a nitrogen atmosphere to obtain a catalyst named 1-Au 25 / Ni 1.5 Mg 1.5 Al-LDH / rGO-300.

[0085] Example 12

[0086] (1) Au 38 Capt 18 Preparation of nanoclusters

[0087] Weigh 1.0g of HAuCl4·4H2O into 100mL of methanol to prepare a 10mg / mL chloroauric acid methanol solution. 24.69mL of the above solution and 0.3804g of TOABr (0.69mmol) were added to a 100mL single-necked flask containing 20.31mL of methanol. The mixture was stirred magnetically at 1200rpm in a 25℃ water bath, and the color of the mixture changed from orange-yellow to dark red. After 15 minutes, 0.3912g of captopril (0.60mmol) was added to the reaction solution, and the color of the solution quickly changed to white. After 30 minutes of reaction, the stirring rate was adjusted to 600rpm, and 15mL of NaBH4 ice water solution was quickly added to the above reaction solution, and the color of the solution immediately changed to brown-green. After the above reaction solution was continuously reacted in a 25±1℃ water bath for 48 hours, it was centrifuged (4800r / min, 20min) to remove the unreacted and insoluble Au(I):Capt polymer. The supernatant was collected and concentrated by rotary evaporation (30°C, 20 min). 20 mL of acetone was added to the concentrate and allowed to stand for 12 hours to obtain precipitated gold clusters. The crude product was then vacuum dried at 30°C for 12 hours to obtain a crude product. The crude product was extracted with methanol for 6 consecutive times (0.5-1 mL each time) to obtain a brown-black transparent extract. 20 mL of acetone was added to the brown-black transparent extract to precipitate the gold clusters again, and centrifuged (3000 r / min, 10 min) to obtain a brown-black precipitate. It was vacuum dried at 30°C for 12 hours to obtain the final brown-black product Au:Capt nanoclusters.

[0088] Polyacrylamide gel electrophoresis separation: The obtained Au:Capt product was separated by polyacrylamide gel electrophoresis (PAGE) at 300V using a vertical gel electrophoresis system. The separation gel and stacking gel were prepared with 30% and 4% acrylamide monomers, respectively. The Au:Capt clusters were dissolved in 10% (v / v) glycerol / water at a concentration of 30 mg / mL and added to the gel at a loading amount of 40 μL / well. After 4 hours of electrophoretic separation, clear bands were cut out from the gel and soaked in water for 2 hours, and the nanocluster solutions mixed with the gel matrix were filtered by using a 0.22 μm filter. Then, after acidification with 10% (v / v) glacial acetic acid, the acidified nanocluster solution was concentrated using a 3 kDa cutoff filter, and finally the concentrate was precipitated with acetone and dried under vacuum to obtain one of the pure black-brown solid powders, which was recorded as Au 38 Capt 24 .

[0089] (2)Ni 1.5 Mg 1.5 The preparation of Al-LDH / rGO hybrid carrier is the same as Example 11.

[0090] (3) Au 38 / Ni 1.5 Mg 1.5 Preparation of Al-LDH / rGO catalyst

[0091] 25mgAu 38 Capt 24 The nanoclusters were dissolved in 100 mL of deionized water to obtain 0.25 mg / mL Au 38 Capt 24 1.0g of Ni 1.5 Mg 1.5 The Al-LDH / rGO hybrid carrier was placed in a 150 mL beaker, and 50 mL of deionized water and an appropriate amount of 0.1 mol / L sodium carbonate solution were added and ultrasonicated for 10 minutes to obtain a hybrid carrier dispersion with a pH of 8.0. 40 mL of 0.25 mg / mL Au 38 Capt 24 Aqueous solution, add an appropriate amount of 0.1 mol / L sodium carbonate solution to pre-adjust the pH to 8.0, add it to the above carrier dispersion under vigorous stirring, the theoretical loading amount of gold nanoclusters is 1.0wt%, stir at 1000rpm for 4 hours. Collect the mixture by centrifugation and freeze-dry to obtain the catalyst precursor Au 38 Capt 24 / Ni 1.5 Mg 1.5 The obtained catalyst precursor was calcined at 280°C for 3 hours in a nitrogen atmosphere to obtain a catalyst named 1-Au38 / Ni 1.5 Mg 1.5 Al-LDH / rGO-280.

[0092] Embodiment 13

[0093] (1) Au ~127 Preparation of -Capt nanoclusters

[0094] Weigh 1.0g of HAuCl4·4H2O into 100mL of methanol to prepare a 10mg / mL chloroauric acid methanol solution. 24.69mL of the above solution and 0.3804g of TOABr (0.69mmol) were added to a 100mL single-necked flask containing 20.31mL of methanol. The mixture was stirred magnetically at 1200rpm in a 25℃ water bath, and the color of the mixture changed from orange-yellow to dark red. After 15 minutes, 0.3912g of captopril (0.60mmol) was added to the reaction solution, and the color of the solution quickly changed to white. After 30 minutes of reaction, the stirring rate was adjusted to 600rpm, and 15mL of NaBH4 ice water solution was quickly added to the above reaction solution, and the color of the solution immediately changed to brown-green. After the above reaction solution was continuously reacted in a 25±1℃ water bath for 48 hours, it was centrifuged (4800r / min, 20min) to remove the unreacted and insoluble Au(I):Capt polymer. The supernatant was collected and concentrated by rotary evaporation (30°C, 20 min). 20 mL of acetone was added to the concentrate and allowed to stand for 12 hours to obtain precipitated gold clusters. The crude product was then vacuum dried at 30°C for 12 hours to obtain a crude product. The crude product was extracted with methanol for 6 consecutive times (0.5-1 mL each time) to obtain a brown-black transparent extract. 20 mL of acetone was added to the brown-black transparent extract to precipitate the gold clusters again, and centrifuged (3000 r / min, 10 min) to obtain a brown-black precipitate. It was vacuum dried at 30°C for 12 hours to obtain the final brown-black product Au. : Capt nanoclusters.

[0095] Polyacrylamide gel electrophoresis separation: The obtained Au:Capt products were separated by polyacrylamide gel electrophoresis (PAGE) at 300 V by using a vertical gel electrophoresis system. Separation gel and stacking gel were prepared with 30% and 4% acrylamide monomer, respectively. Au:Capt clusters were dissolved in 10% (v / v) glycerol / water at a concentration of 30 mg / mL and added to the gel at a loading amount of 40 μL / well. After 4 h of electrophoretic separation, clear bands were cut out from the gel and soaked in water for 2 h, and these nanocluster solutions mixed with gel matrix were filtered by using a 0.22 μm filter. Then, after acidification by adding 10% (v / v) glacial acetic acid, a 3 kDa cutoff filter was used to concentrate the acidified nanocluster solution, and finally the concentrate was precipitated with acetone and dried under vacuum to obtain one of the pure black-brown solid powders, and one of the larger black-brown solid powders was obtained by drying under vacuum. We used a simple method, assuming that the gold nanoclusters are spherical and their density is the same as that of bulk Au. Based on the size of ~1.6 nm obtained by TEM analysis, we calculated that the larger-sized gold nanoclusters correspond to Au~127-Capt.

[0096] (2)Ni 1.5 Mg 1.5 The preparation of Al-LDH / rGO hybrid carrier is the same as Example 11.

[0097] (3) Au ~127 / Ni 1.5 Mg 1.5 Preparation of Al-LDH / rGO catalyst

[0098] 25mgAu ~127 -Capt nanoclusters were dissolved in 100 mL of deionized water to obtain 0.25 mg / mL Au 38 Capt 24 1.0g of Ni 1.5 Mg 1.5 The Al-LDH / rGO hybrid carrier was placed in a 150 mL beaker, and 50 mL of deionized water and an appropriate amount of 0.1 mol / L sodium carbonate solution were added and ultrasonicated for 10 minutes to obtain a hybrid carrier dispersion with a pH of 8.0. 40 mL of 0.25 mg / mL Au ~127 -Capt aqueous solution, add an appropriate amount of 0.1 mol / L sodium carbonate solution to pre-adjust the pH to 8.0, add it to the above carrier dispersion under vigorous stirring, the theoretical loading amount of gold nanoclusters is 1.0wt%, stir at 1000rpm for 4 hours. Collect the mixture by centrifugation and freeze-dry to obtain the catalyst precursor Au ~127 -Capt / Ni 1.5 Mg 1.5The obtained catalyst precursor was calcined at 280°C for 3 hours in a nitrogen atmosphere to obtain a catalyst named 1-Au ~127 / Ni 1.5 Mg 1.5 Al-LDH / rGO-280.

[0099] Embodiment 14

[0100] (1) Au 25 Capt 18 The preparation of nanoclusters is the same as in Example 1.

[0101] (2) Preparation of Mg3Al-LDH / rGO hybrid support

[0102] Mix Mg(NO3)2·6H2O and Al(NO3)3·9H2O in a molar ratio of [Mg 2+ ] / [A1 3+ ]=3, and the other synthesis steps are the same as those in Example 1.

[0103] (3) Au 25 Preparation of / Mg3Al-LDH / rGO catalyst

[0104] The synthesis steps are the same as those in Example 2. 25 Capt 18 The catalyst was prepared by calcining / Mg3Al-LDH / rGO at 280 °C for 3 h in a nitrogen atmosphere and named 0.5-Au 25 / Mg3Al-LDH / rGO-280.

[0105] Embodiment 15

[0106] (1) Au 25 Capt 18 The preparation of nanoclusters is the same as in Example 1.

[0107] (2) Preparation of Co3Al-LDH / rGO hybrid support

[0108] Co(NO3)2·6H2O and Al(NO3)3·9H2O were mixed in a molar ratio of [Co 2+ ] / [A1 3+ ]=3, and the other synthesis steps are the same as those in Example 1.

[0109] (3) Au 25 Preparation of / Co3Al-LDH / rGO catalyst

[0110] The synthesis steps are the same as those in Example 2. 25 Capt 18The catalyst was prepared by calcining / Co3Al-LDH / rGO at 280 °C for 3 h in a nitrogen atmosphere and named 0.5-Au 25 / Co3Al-LDH / rGO-280.

Claims

1. A multi-level structure hybrid supported atomic precision gold nanocluster catalyst, characterized in that: The expression is Au n / (M 2 + )Al-LDH / rGO-T, where Au n is n gold atoms, n = 25, 38; (M 2+ )Al-LDH / rGO 2+ Mg 2+ 、Ni 2+ 、Co 2+ Any one or two of ions; size of 55-70nm and thickness of 8-10nm (M 2+ )Al-LDH nanosheets grow vertically and staggered on both sides of rGO sheets, showing a nanosheet array morphology; gold nanoclusters with sizes of 1.0±0.3, 1.5±0.3 and 1.8±0.4 nm in the catalyst are highly dispersed at the edge of LDH and at the junction of LDH and rGO; the active component in the catalyst is gold nanoclusters, and its mass percentage is 0.5-1.5%; The preparation method of the catalyst comprises the following steps: (1) Preparation of gold nanocluster precursors Preparation of Au by combining size focusing and polyacrylamide gel electrophoresis 25 Capt 18 、Au 38 Capt 24 Nanoclusters; First, 1g of tetrahydrated chloroauric acid was dissolved in 100mL of methanol to prepare a 10mg / mL chloroauric acid methanol stock solution; Then, 8.23mL of tetrahydrated chloroauric acid methanol solution and 126.8mg of tetraoctylammonium bromide were added to a 100mL round-bottom flask filled with 6.75mL of methanol, and magnetically stirred at 1200rpm at room temperature, and the mixture changed from orange-yellow to dark red; After 15 minutes of reaction, 130.4mg of captopril (Capt) was added to the reaction solution, and the color of the solution quickly changed to white; After 30 minutes of reaction, the stirring rate was adjusted to 600rpm, and 5mL of 37.8mg The icy aqueous solution of NaBH4 was quickly added to the above reaction solution, and the color of the solution immediately changed to brown-green; after the above reaction solution was reacted in a water bath at 25±1°C for 48 hours, the reaction solution was centrifuged at 5000r / min for 20min to remove the unreacted and insoluble Au(I):Capt polymer; the supernatant was collected and rotary evaporated at 30°C for 20min to obtain a concentrated solution; 20mL of acetone was added to the concentrated solution and allowed to stand for 12 hours to obtain precipitated gold clusters; then vacuum dried at 30°C for 12 hours to obtain a crude product; the crude product was continuously extracted with 0.5-1mL of methanol for 6 times to obtain a brown-black transparent extract; 20mL of acetone was added to the brown-black transparent extract to precipitate the gold clusters again, and centrifuged at 3000r / min for 10min to obtain a brown-black precipitate; it was vacuum dried at 30°C for 12 hours to obtain a brown-black product Au : Capt nanoclusters; Polyacrylamide gel electrophoresis separation: The obtained Au:Capt nanoclusters were separated by polyacrylamide gel electrophoresis at 300V by using a vertical gel electrophoresis system; 30% and 4% acrylamide monomers were used to prepare separation gel and stacking gel, respectively; Au:Capt nanoclusters were dissolved in 10% v / v glycerol / water at a concentration of 30 mg / mL and added to the gel at a loading amount of 40 μL / well; after 4 hours of electrophoretic separation, clear bands were cut out from the gel and immersed in water for 2 hours, and the nanocluster solutions mixed with the gel matrix were filtered by using a 0.22 μm filter; then, after acidification with 10% v / v glacial acetic acid, the acidified nanocluster solution was concentrated using a 3 kDa cutoff filter, and finally the concentrate was precipitated with acetone and dried under vacuum for 12 hours to obtain pure Au 25 Capt 18 and Au 38 Capt 24 and larger-sized gold nanoclusters; (2) Preparation of nanosheet array-like hierarchical structured LDH / rGO hybrid carrier Firstly, natural flake graphite powder was used as raw material, and graphene oxide sol with a mass concentration of 8.07 mg / mL was prepared by the improved Hummers method as a stock solution; then, a nanosheet array structure (M 2+ )Al-LDH / rGO hybrid; the specific steps are as follows: 50 mg GO sol was dispersed into 100 mL deionized water, ultrasonically exfoliated for 20 minutes, and then 25 mg citric acid was added and ultrasonicated for 5 minutes; the obtained citric acid-modified GO suspension was transferred to a 500 mL four-necked flask, and a mixed alkaline solution of NaOH and Na2CO3 was added dropwise under vigorous stirring until the pH was 10.0±0.1, and stabilized for 10 minutes, wherein OH - and CO3 2- The substance concentration ratio is 3.2; then 100mL (M 2+ )(NO3)2·6H2O and Al(NO3)3·9H2O mixed salt solution, and at the same time add mixed alkali solution to make the pH value of the mixed system 10.0±0.1, where CO3 2- and Al 3+ The molar concentration ratio of M is 3.

2. 2+ Mg 2+ 、Ni 2+ 、Co 2+ Any one or two of the ions, M 2+ and Al 3+ The total amount of substance is 20mmol, M 2+ and Al 3+ The molar concentration ratio of the substance is 3; after the dropwise addition, the obtained mixed solution is crystallized in a 65°C water bath for 4 hours; finally, it is separated by centrifugation, washed with deionized water until neutral, and freeze-dried to obtain a multi-level structure hybrid carrier, named (M 2+ )Al-LDH / rGO; (3) Preparation of nanosheet array-like hierarchical structured LDH / rGO loaded atomically precise gold nanocluster catalysts Preparation of Au by pH dual-controlled electrostatic adsorption n / (M 2+ )Al-LDH / rGO-T catalyst, the specific operation steps are as follows: 0.5-1.0g (M 2+ ) The Al-LDH / rGO hybrid carrier is added to 30-50 mL of deionized water, and an appropriate amount of Na2CO3 solution with a molar concentration of 0.1 mol / L is added and ultrasonically adjusted for 5-15 minutes to obtain a carrier dispersion with a pH of 6.0-10.0; a certain amount of a gold nanocluster precursor solution pre-adjusted to pH 6.0-10.0 by a Na2CO3 solution with a molar concentration of 0.1 mol / L is added to the above carrier dispersion under vigorous stirring at room temperature, and the theoretical loading amount of the gold nanocluster is 0.5-1.5 wt %, and the reaction is carried out under magnetic stirring at 1000 rpm for 2-6 hours; the mixture is collected by centrifugation, and freeze-dried to obtain a catalyst precursor; the obtained catalyst precursor is calcined at 260-300° C. in a nitrogen atmosphere for 3 hours to obtain a catalyst, which is named Au n / (M 2+ )Al-LDH / rGO-T.

2. A method for preparing the multi-level structure hybrid supported atomic precision gold nanocluster catalyst according to claim 1, characterized in that: The following steps are involved: (1) Preparation of gold nanocluster precursors Preparation of Au by combining size focusing and polyacrylamide gel electrophoresis 25 Capt 18 、Au 38 Capt 24 ; First, 1 g of tetrahydrate chloroauric acid was dissolved in 100 mL of methanol to prepare a 10 mg / mL chloroauric acid methanol stock solution; then, 8.23 ​​mL of tetrahydrate chloroauric acid methanol solution and 126.8 mg of tetraoctylammonium bromide were added to a 100 mL round-bottom flask containing 6.75 mL of methanol, and magnetically stirred at 1200 rpm at room temperature, and the mixed solution changed from orange-yellow to dark red; after 15 minutes of reaction, 130.4 mg of captopril (Capt) was added to the reaction solution, and the solution color quickly changed to white; after 30 minutes of reaction, the stirring rate was adjusted to 600 rpm, and 5 mL of 37.8 mg of The icy aqueous solution of NaBH4 was quickly added to the above reaction solution, and the color of the solution immediately changed to brown-green; after the above reaction solution was reacted in a water bath at 25±1°C for 48 hours, the reaction solution was centrifuged at 5000r / min for 20min to remove the unreacted and insoluble Au(I):Capt polymer; the supernatant was collected and rotary evaporated at 30°C for 20min to obtain a concentrated solution; 20mL of acetone was added to the concentrated solution and allowed to stand for 12 hours to obtain precipitated gold clusters; then vacuum dried at 30°C for 12 hours to obtain a crude product; the crude product was continuously extracted with 0.5-1mL of methanol for 6 times to obtain a brown-black transparent extract; 20mL of acetone was added to the brown-black transparent extract to precipitate the gold clusters again, and centrifuged at 3000r / min for 10min to obtain a brown-black precipitate; it was vacuum dried at 30°C for 12 hours to obtain a brown-black product Au : Capt nanoclusters; Polyacrylamide gel electrophoresis separation: The obtained Au:Capt nanoclusters were separated by polyacrylamide gel electrophoresis at 300V by using a vertical gel electrophoresis system; 30% and 4% acrylamide monomers were used to prepare separation gel and stacking gel, respectively; Au:Capt nanoclusters were dissolved in 10% v / v glycerol / water at a concentration of 30 mg / mL and added to the gel at a loading amount of 40 μL / well; after 4 hours of electrophoretic separation, clear bands were cut out from the gel and immersed in water for 2 hours, and the nanocluster solutions mixed with the gel matrix were filtered by using a 0.22 μm filter; then, after acidification with 10% v / v glacial acetic acid, the acidified nanocluster solution was concentrated using a 3 kDa cutoff filter, and finally the concentrate was precipitated with acetone and dried under vacuum for 12 hours to obtain pure Au 25 Capt 18 and Au 38 Capt 24 and larger-sized gold nanoclusters; (2) Preparation of nanosheet array-like hierarchical structured LDH / rGO hybrid carrier Firstly, natural flake graphite powder was used as raw material, and graphene oxide sol with a mass concentration of 8.07 mg / mL was prepared by the improved Hummers method as a stock solution; then, a nanosheet array structure (M 2+ )Al-LDH / rGO hybrid; the specific steps are as follows: 50 mg GO sol was dispersed into 100 mL deionized water, ultrasonically exfoliated for 20 minutes, and then 25 mg citric acid was added and ultrasonicated for 5 minutes; the obtained citric acid-modified GO suspension was transferred to a 500 mL four-necked flask, and a mixed alkaline solution of NaOH and Na2CO3 was added dropwise under vigorous stirring until the pH was 10.0±0.1, and stabilized for 10 minutes, wherein OH - and CO3 2- The substance concentration ratio is 3.2; then 100mL (M 2+ )(NO3)2·6H2O and Al(NO3)3·9H2O mixed salt solution, and at the same time add mixed alkali solution to make the pH value of the mixed system 10.0±0.1, where CO3 2- and Al 3+ The molar concentration ratio of M is 3.

2. 2+ Mg 2+ 、Ni 2+ 、Co 2+ Any one or two of the ions, M 2+ and Al 3+ The total amount of substance is 20mmol, M 2+ and Al 3+ The molar concentration ratio of the substance is 3; after the dropwise addition, the obtained mixed solution is crystallized in a 65°C water bath for 4 hours; finally, it is separated by centrifugation, washed with deionized water until neutral, and freeze-dried to obtain a multi-level structure hybrid carrier, named (M 2+ )Al-LDH / rGO; (3) Preparation of nanosheet array-like hierarchical structured LDH / rGO loaded atomically precise gold nanocluster catalysts Preparation of Au by pH dual-controlled electrostatic adsorption n / (M 2+ )Al-LDH / rGO-T catalyst, the specific operation steps are as follows: 0.5-1.0g (M 2+ ) The Al-LDH / rGO hybrid carrier is added to 30-50 mL of deionized water, and an appropriate amount of Na2CO3 solution with a molar concentration of 0.1 mol / L is added and ultrasonically adjusted for 5-15 minutes to obtain a carrier dispersion with a pH of 6.0-10.0; a certain amount of a gold nanocluster precursor solution pre-adjusted to pH 6.0-10.0 by a Na2CO3 solution with a molar concentration of 0.1 mol / L is added to the above carrier dispersion under vigorous stirring at room temperature, and the theoretical loading amount of the gold nanocluster is 0.5-1.5 wt %, and the reaction is carried out under magnetic stirring at 1000 rpm for 2-6 hours; the mixture is collected by centrifugation, and freeze-dried to obtain a catalyst precursor; the obtained catalyst precursor is calcined at 260-300° C. in a nitrogen atmosphere for 3 hours to obtain a catalyst, which is named Au n / (M 2+ )Al-LDH / rGO-T.